Implikasi Kebijakan Perdagangan ACFTA Pada Bawang Putih Impor di Indonesia: Model Permintaan Impor - Inggarani Ulfa Yovirizka; Tri Haryanto (MediaTrend, 2020)
Indonesia is the biggest importer of garlic in the world. Each country has a trade policy to control imports, and Indonesia is implementing a free trade agreement, namely ACFTA. The purpose of this study was to analyze the effect of the ACFTA trade policy on Indonesian garlic using the import demand model. The method in this study uses the Eagle-Granger cointegration test and error correction model (ECM). Stationary test results using augmented Dickey-Fuller indicate that each stationary variable at the first difference level. Cointegration test shows that import variables, per capita income, relative prices, production and consumption ratios, and dummy have a long-term balance. The relative price, the ratio of production and consumption, and the dummy have a significant effect on the demand for imported garlic in the long run. In the short term, import demand is affected by the ratio of production and consumption, and dummy tariffs.